PEMBIASAAN LITERASI DASAR MELALUI KEGIATAN MEMBACA PADA SISWA SD IT EL-FATAH - Yustika Irfani Lindawati; Putri Tunggal Dewi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Basic literacy habituation through reading activities for SD IT El-Fatah students is a service program that aims to empower the community of SD IT El-Fatah through basic reading literacy activities. The main target in this program is grade III students. The series of service activities start from the planning stage to identify the needs and strengths of students and schools. The results show that reading facilities and infrastructure in schools are not adequate and students' reading interest is still low, so plans are made to create a reading corner and a reading literacy habituation program. The implementation stage is the actualization of the plan to produce a reading corner equipped with a collection of children's story books, followed by the application of basic literacy habits through reading to third-grade students. The results of the implementation of basic literacy habituation are written on reading cards and analyzed for evaluation. Based on the results of habituation of basic literacy reading, it is known that 1) the existence of a reading corner and habituation of basic literacy reading received a positive response from students; 2) students experienced an increase in reading interest as seen from the increase in the number of pages read per day; 3) the diversity in students' reading skills can be seen from the different average number of pages that students can read per day; 4) the existence of a reading corner and a basic literacy habituation program are factors that can influence students' reading interest in terms of environmental factors and facilities.